Women’s Value In A Social Capital Context: A Net Present Social Value Analysis - Stephen Ayoade Fadare (International Journal of Business Studies, 2022)
Social capital is formed from individual abilities through the social investment that contributes to value creation where individuals feel a sense of membership and commitment through their social interactions and relationships. This study aims to explore the application of social capital to women's organizations. It further explores the net social value of women's organizations and the women members to determine social capital's role as a means for value creation. At these ends, the mixed method was employed by combining qualitative and quantitative data gathering approaches. The study used key informant interviews among 11 women's organizations in Baguio City and Benguet, where a total of 284 women members were interviewed. The result of the talks was subjected to semantic analysis and net present social value analysis. The results reveal that women's organizations reflect the dimensions of social capital and bring a significant contribution to members' lives. The findings imply that women members are duly recognized in their organizations, and each member expects to receive a positive value of the social benefit. Hence, women's organizations are the embodiment of social capital that contributes to women's value creation and empowers their members to maximize their capacities.